RESTORATIVE JUSTICE DAN REFORMULASI SANKSI PIDANA NARKOBA ANALISIS KRITIS IMPLEMENTASI UU PENYESUAIAN PIDANA DAN KEBIJAKAN REHABILITATIF DALAM PERSPEKTIF HUKUM - Aditya Putra Setyawan; Siti Humulhaer; Muhammad Fajar Alfahimi; Wisnu Cahyo Apriliyadi; Dwi Mani Suci Purwanto (CV. Lafadz Jaya, 2026)
This study analyzes recent developments in Indonesia’s drug policy following the enactment of Law Number 1 of 2025 on Sentencing Adjustment and the ongoing revision of Law Number 35 of 2009 on Narcotics, which has been proposed for inclusion in the 2025 Priority National Legislative Program (Prolegnas). The analysis focuses on the transformation of sentencing paradigms from a conventional retributive approach toward a restorative justice and rehabilitative approach, as well as the implications of abolishing special minimum penalties in narcotics cases on judicial discretion. This research employs a normative legal research method using conceptual, statutory, and philosophical approaches. The findings indicate that the Sentencing Adjustment Law has created broader space for judicial independence in imposing criminal sanctions, accommodated judicial practices reflected in Supreme Court Circular Letters (SEMA), and provided legitimacy for the application of restorative justice mechanisms for narcotics users. However, conceptual challenges remain regarding the use of the term restorative justice in the context of narcotics offenses, which are often categorized as victimless crimes and may be more appropriately addressed through a rehabilitation-oriented framework based on a medical model. This study recommends the harmonization of the Sentencing Adjustment Law with the ongoing revision of the Narcotics Law, the strengthening of rehabilitation facilities, and the development of specialized drug courts as dedicated institutions for handling narcotics-related cases.